Metafysik og Åbenbaring. Om de tradiske, respektive trinitariske strukturer i N. F. S. Grundtvigs tænkning 1812-1815 - Pedersen, Kim Arne (Grundtvig-studier, 1995)
Metaphysics and Revelation. About the Triadic or, respectively, Trinitarian Structures cin N.F.S. Grundtvig’s Thinking 1812-1815A lecture for the Ph.D. degree in theology, University of Aarhus, March, 1995, on the basis of the thesis: Studies in the Relationship between Metaphysics and Faith in Grundtvig’s Writings in the Period 1812 - 1815, Aarhus 1994.By Kim Arne Pedersen The present Ph.D. lecture has been worked out on the basis of a title given by the Assessment Committee. In the lecture the title is understood to imply that the Committee requires a balanced discussion of whether Grundtvig chooses revelation or metaphysics, understood as natural theology, as the source of man’s knowledge of God. While, in his Ph.D. thesis, the writer consistently spoke in terms of Trinitarian structures in Grundtvig’s writings, the Assessment Committee operates with a distinction between Triadic and Trinitarian structures, implying a parallel to the distinction between metaphysics and revelation. The present writer understands the question as pertaining to a revelation-theological, Aarhus-inspired tradition in the interpretation of Grundtvig, which sees the revelation of Christ in the church service as the point of departure for the recognition of God’s Trinity. In the beginning of the lecture a number of crucial positions in Grundtvig research are outlined. The overall issue is contained in the discussion between Kaj Thaning and recent research, i.e. the discussion whether, from 1832, Grundtvig separates human life from Christianity (Thaning) or whether Grundtvig partly operates with a connection between human life and Christianity, and partly both separates these entities and maintains their interaction. The more specific set of issues is represented, on one hand, by Grell’s view that, in his Danne-Virke period, Grundtvig upholds a distinction between natural and revealed theology, and on the other hand by Henning Høirup’s and William Michelsen’s understanding of Grundtvig’s Danne-Virke thinking as a form of recognition of faith. In addition to the discussion with these Grundtvig scholars the writer deals with Regin Prenter’s work on Grundtvig’s Trinitarian theology, where, in continuation of the interaction model and within the framework of the Aarhus-inspired, revelation-theological understanding of Grundtvig, his Trinitarian theology is interpreted as relational, since Prenter understands Grundtvig’s emphasis on God the Father’s aseity as determined by the Father’s relationship to the other personae of the Trinity. The Grundtvig scholars mentioned here all agree in emphasizing the metaphysical-critical dimension in Grundtvig’s thinking, though Prenter does so only with certain modifications. The lecturer follows Helge Grell in the view that Grundtvig makes a distinction between natural and revealed theology, but at the same time explains how Grundtvig, in this connection, operates with a natural-theological concept of faith, independent of the revelation in Christ. Taking its starting-point in the included textual edition of Fascicle 85, About Faith and Its Relation to Our Life on Earth, Or About Church and State, 1813, the lecture demonstrates how Grundtvig determines faith as the lodestar to human cognition. The human recognition of God arises through the cooperation of the three faculties of cognition, imagination, emotion and reason. This human recognition is truly man’s own, and therefore has a limited independence in comparison with faith, the ruling principle. However, the obscure, unverifiable knowledge of God ultimately rests with God’s unceasing and sustaining creation of man, in the process of which God as the Holy Spirit makes use of man’s imagination. Human recognition springs from the faculties of cognition, triadically understood, and must proceed on the basis of those to reach a verifiable recognition of God, a recognition that is not direct, but metaphorical. This metaphorical recognition has the triadic structure of the human faculties of cognition as their basis and therefore includes a natural-theological understanding of God’s Trinity. Thus, the recognition of God’s Trinity is not primarily linked to the revelation in Christ, but has a naturaltheological point of departure. When Grundtvig bases the recognition of the divine Trinity on the human Triad, he harks back to the Augustinian psychological doctrine of the Trinity as carried on in a post-Reformation tradition - without carrying this tradition to its extreme conclusion which would reduce the divine personae to mere forms of existence in the one divine subject. Grundtvig takes this psychological doctrine of the Trinity as the starting-point for the accomplishment of a natural-theological recognition of God, which at the same time is christologically determined by the idea of the Son as the creative LOGOS. The Fall prevents this LOGOS-oriented, natural-theological recognition of God which, consequently, can only be re-established in, and through, the Incarnation of Christ. To a very great extent, therefore, the present writer finds himself in agreement with the Aarhus-inspired, theological Grundtvig interpretation which emphasizes that the revelation in Christ, linked by Grundtvig to the church service from the 1820s, is the point of departure for the inter-action between what is Christian and what is human which, with the human likeness to God as a medium, becomes allcomprehensive and thus metaphysical. Semantically it makes sense to distinguish between Triadic and Trinitarian structures in Grundtvig’s writings, such as the Assessment Committee does. But this must not prevent Grundtvig research from recognizing that he operates with a natural-theological recognition of God’s Trinity with the human Triadic structure as a starting-point. Likewise, the relational interpretation of Grundtvig’s Trinitarian theology must not obstruct the understanding of the metaphysical implications in Grundtvig’s theology of creation, as they find expression in his descriptions of God the Father’s aseity.